2020
DOI: 10.1371/journal.pone.0229875
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary tuberculosis in HIV-infected patients in rural Tanzania: The prospective Kilombero and Ulanga antiretroviral cohort

Abstract: BackgroundIn sub-Saharan Africa, diagnosis and management of extrapulmonary tuberculosis (EPTB) in people living with HIV (PLHIV) remains a major challenge. This study aimed to characterize the epidemiology and risk factors for poor outcome of extrapulmonary tuberculosis in people living with HIV (PLHIV) in a rural setting in Tanzania. MethodsWe included PLHIV >18 years of age enrolled into the Kilombero and Ulanga antiretroviral cohort (KIULARCO) from 2013 to 2017. We assessed the diagnosis of tuberculosis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…Nigeria is ranked as one of the 30 high TB burden countries in the world and it has incidence rate of 219 per 100,000 populations with an estimated 12% of the cases co-infected with HIV [4]. Extra Pulmonary TB (EPTB) is very common among people living with HIV (PLWH) in sub Saharan Africa and it accounts for high mortality and loss to follow up [5,6]. The prevalence of EPTB among notified TB cases in Africa region in 2017 was 16%, next to the highest Eastern Mediterranean region (24%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria is ranked as one of the 30 high TB burden countries in the world and it has incidence rate of 219 per 100,000 populations with an estimated 12% of the cases co-infected with HIV [4]. Extra Pulmonary TB (EPTB) is very common among people living with HIV (PLWH) in sub Saharan Africa and it accounts for high mortality and loss to follow up [5,6]. The prevalence of EPTB among notified TB cases in Africa region in 2017 was 16%, next to the highest Eastern Mediterranean region (24%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in line with the previous reports. The published literature shows that extrapulmonary TB is more common in the HIV-associated TB population, it becomes increasingly prevalent with progressive immunodeficiency, and it contributes to unfavorable TB treatment outcomes [ 21 , 22 , 23 , 24 , 25 ]. A study conducted in sub-Saharan Africa showed that extrapulmonary TB was associated with an increased risk of unfavorable outcomes such as death and lost to follow-up among patients with HIV-associated TB [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increases the risk of development of the disease, either by primary TB infection or by reactivation of latent TB infection. Studies from 2018 show that HIV increases the risk of TB by about 19 times (range [15][16][17][18][19][20][21][22] [6]. Among untreated PLHIV, the risk of reactivation of latent TB infection is 3-16% annually, which is almost the same as the lifetime risk of TB in people without HIV (5-10%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…En pacientes con VIH avanzado con recuento de células CD4 < 250 células/mm, la progresión de la enfermedad es marcadamente diferente en comparación con los pacientes con recuento de células CD4 más alto (6) . El diagnóstico sigue siendo un desafío, ya que las manifestaciones clínicas son diversas, las pruebas microbiológicas dependen de procedimientos invasivos y el gold standard del cultivo de micobacterias o la histopatología de apoyo no está disponible en su mayoría (7) . Reportamos una presentación inusual de TB multisistémica que afectó el sistema urinario, respiratorio y digestivo de un paciente varón de 19 años inmunodeprimido por VIH.…”
Section: Introductionunclassified